Talisay Tree (Terminalia Catapa) Nut Spread - Carpio Chrishamay C.,; Compleza Krayzel Ann S.; Faling Ma. Novie N.; Panergar Mary Vhince F; Sanogal Joylyn C.; Sarabia Pathy Marie S.; Sasa, Mary Rojannie S.; Venecio Zoe M. (IC-ITECHS, 2022)
Talisay tree is commonly found along coastal areas, roadsides and parks, it is adapted to this type of habitat because it is salt and drought tolerant, best grown under full sun and is also resilient to strong winds during the rainy season. This tree is grown for its ornamental purposes and its edible nuts. This experimental study determined the level of acceptability of Talisay Tree (Terminalia Catappa) Nut Spread as to appearance, aroma, taste, texture and general acceptability in two formulations. This study also determined if there was a significant difference in the level of perception of the evaluators among the two formulations of Talisay Tree (Terminalia Catappa) Nut Spread. A survey questionnaire was used in gathering the data. The evaluators of the study were the thirty (30) nut spread vendors and consumers of Brgy. Qui-anan San Joaquin, Iloilo. Based on the results of the study, the appearances of the two formulations were perceived as “Light Brown” for the Formulation A and “Dark Brown” for the Formulation B. For the aroma, it was perceived as “Moderately Strong Talisay Nut aroma” for Formulation A and “Very Strong Talisay Nut aroma” for Formulation B. For the texture, both formulations was perceived “Very Smooth Talisay Nut” spread. In terms of taste, Formulation A has a “Very Pleasing Talisay Nut taste” and Formulation B has “Extremely Pleasing Talisay Nut Taste”. Inferential statistics revealed that there is a significant difference in the sensory characteristics and the level of acceptability of talisay nut spread in terms of appearance, aroma, taste and texture. As to the general acceptability, both formulation A and B were “Liked Very Much”. This implies that both sweetener used specifically the granulated sugar and muscovado sugar prepared by the researchers made an impact to the sensory acceptability of the spread. Thus, Talisay Nut Spread has the potential to be used as another flavored spread. It is recommended that further studies related to this research using other variables is encouraged to glorify other factors that relates to the Level of Acceptability of Talisay Nut Spread.